(untitled) (Research, Society and Development, 2021)
Systemic Arterial Hypertension is one of the most prevalent risk factors for the emergence of Chronic Noncommunicable Diseases. The Framingham Risk Score (ERF) is applied to detect cardiovascular risks over a 10- year period, based on age, gender, systolic blood pressure, total cholesterol, HDL cholesterol fraction and smoking. The present study aimed to identify the cardiovascular risk of hypertensive patients seen at a Basic Health Unit in the Municipality of Piripiri-PI, through the evaluation by the Framingham Risk Score. The study was a descriptive field research with a cross-sectional and quantitative approach, the research participants were hypertensive patients of both sexes registered in the Family Health Strategy (FHS) 20 shuttlecocks in the urban area in the Municipality of Piripiri-PI. Hypertensive patients aged 20 to 79 years, enrolled in the FHS 20 Shuttlecocks, with Total Cholesterol and HDL-Cholesterol tests performed in the last three months participated in the sample. Data were collected after signing the Informed Consent Form (ICF) by each patient, authorizing their participation. Through data collection and application of the ERF, it was possible to assess the cardiovascular risk of hypertensive participants, where 66.67% of the participants were at low risk and 33.33% demonstrated a moderate risk of developing a Cardiovascular Disease (CVD) in 10 years. Therefore, it is concluded that despite the majority of the studied hypertensive individuals present low to moderate risk of developing CVD in 10 years, the performance of the multiprofessional team in monitoring the risk factors and precaution of a possible complication is necessary and important.